2012
DOI: 10.1152/japplphysiol.01391.2011
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin administration acutely stimulates resting energy expenditure in healthy young men

Abstract: Treatment with recombinant human erythropoietin (rHuEpo) improves insulin sensitivity in patients with end-stage renal disease, and animal studies indicate that Epo increases fat oxidation. However, the metabolic effects of rHuEpo have never been experimentally studied in healthy humans. The aim was to investigate the effects of an acute rHuEpo bolus on substrate metabolism and insulin sensitivity in healthy young men. Ten healthy young men were studied in a single-blinded, randomized crossover design with a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 43 publications
5
33
2
1
Order By: Relevance
“…In support of this, adipose tissue specific deletion of Epo-R in mice did not significantly alter whole-body energy expenditure or RQ values [15]. Resting energy expenditure significantly increased in the current studies, and fat oxidation tended to be increased in relation to rHuEpo treatment [6,7]. The effect of Epo on POMC was not Fig.…”
Section: Direct and Indirect Effects Of Epo On Lipolysissupporting
confidence: 71%
See 2 more Smart Citations
“…In support of this, adipose tissue specific deletion of Epo-R in mice did not significantly alter whole-body energy expenditure or RQ values [15]. Resting energy expenditure significantly increased in the current studies, and fat oxidation tended to be increased in relation to rHuEpo treatment [6,7]. The effect of Epo on POMC was not Fig.…”
Section: Direct and Indirect Effects Of Epo On Lipolysissupporting
confidence: 71%
“…Studies in end-stage renal disease (ERSD) patients show that serum levels of triglycerides, total cholesterol, and LDL decrease to normal levels after Epo treatment [3][4][5], but acute administration of rHuEpo in healthy subjects do not significantly affect lipid levels, although a tendency to increased free fatty acid (FFA) levels have been observed [6]. However, prolonged treatment to healthy humans with an erythropoiesis-stimulating agent (ESA) significantly increases serum FFA levels and hepatic lipid content [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and human studies evaluating the metabolic effects of erythropoietin mainly show increases in RER and protection against high-fat-diet-induced obesity by an increased muscle fat oxidation (Christensen, Lundby, et al, 2012;Christensen et al, 2013;Hojman et al, 2009;Meng, Zhu, Bi, Yang, & Wang, 2013). In young healthy males, Christensen, Vendelbo, et al (2012) demonstrated that RER was higher after an acute high dose (400 IU · kg −1 ) infusion of recombinant erythropoietin, together with a tendency for an increased basal whole body fat oxidation. However, specific energy sensing muscle key proteins regulating influx of fatty acids to the mitochondria, such as AMP-activated protein kinase and Acetyl CoA carboxylase were not altered by the treatment.…”
mentioning
confidence: 99%
“…Mikolás et al 64 observaram também perda de peso em animais tratados com rHuEPO. Além disto, Christensen et al 65 , após investigarem os efeitos da administraç ão aguda de rHuEPO sobre o metabolismo da sensibilidade à insulina em indivíduos jovens saudáveis, observaram aumento do gasto energético em resposta à administraç ão de uma única dose do hormônio (400 UI/kg). Adicionalmente, já foi relatado que a rHuEPO está relacionada com a prevenç ão de lesão renal aguda, em um modelo experimental de treinamento físico de alta intensidade, em virtude de seu efeito antiapoptótico 66 .…”
Section: Efeitos Da Eritropoietina Humana Recombinante Sobre O Desempunclassified